Early auditory preverbal skills development in Mandarin speaking children with cochlear implants. Issue 1 (January 2015) - Liu, Haihong; Jin, Xin; Li, Jing; Liu, Lulu; Zhou, Yi; Zhang, Jie; Ge, Wentong; Ni, Xin
Abstract Objective The purpose of this study was to investigate the development of auditory preverbal skills in Mandarin speaking infants/toddlers with cochlear implants (CIs). Methods Participants were recruited from the Pediatric Audiology Center of Beijing Children's Hospital, Capital Medical University. A total of 33 children with severe-to-profound hearing loss who received CIs participated in the study. The evaluation tools were LittlEARS® Auditory Questionnaire (LEAQ) and self-designed demographic information questionnaire. Evaluations were administrated immediately after the CI was switched on (0-month), and at 1, 3, 6, 9, 12, 18, and 24-month intervals of CI use. Results The mean total scores of the LEAQ in 0, 1, 3, 6, 9, 12, 18, and 24-month were 1, 5, 10, 15, 21, 24, 30, and 33 points, respectively. The developmental trajectory of early auditory preverbal skills in the CI children was consistent with the published norm data of the LEAQ, and the expected value even slightly higher than the norms. Analysis showed that the parents' level of education and age of implantation influenced the final LEAQ score significantly (ANOVA, p < 0.0001). Conclusions Auditory preverbal skills improved dramatically after cochlear implantation in the first 2 years of implant use. Early implanted children exhibited a steeper and faster improvement in auditory preverbal developmental compared to the later implanted peers. This study described the developmental trajectories of preverbal auditory skills and confirmed the effectiveness of early implantation on the development of auditory preverbal skills. The results could provide guidance for auditory/speech rehabilitation in Mandarin speaking infants/toddlers who received CIs in their early age.